Faculty of Mechanical Engineering: Research Guide (University of Maribor Press, 2025)
The publication presents an overview of research activities and research achievements at the Faculty of Mechanical Engineering. The following research areas are presented: Energy, process and environmental engineering, Construction and design, Materials technology, Mechanics, Production engineering, Textile materials and design, and Fundamental and general areas. Individual laboratories and centers of the faculty present their research equipment, service offerings for industry, collaborations with companies and other institutions, the most prominent publications, patents, national and international projects and the most important research achievements.